2012
DOI: 10.4103/0974-2700.93106
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork in the trauma room evaluation of a multimodal team training program

Abstract: Introduction:Poor teamwork leads to preventable medical errors, and thus negatively impacts medical care. One way to improve teamwork is training. A multimodality team training program was designed to impact the attitudes and behavior of first-year residents who will encounter medical situations in the trauma room. The training program included low-fidelity role plays, lectures, and high-fidelity simulation with feedback.Materials and Methods:The training program was a one-day workshop that was conducted twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…These groups were analyzed subsequently using the GRADE system in Table II. Six studies 9,20,25,28,29,31 reported on more than one outcome and were included in more than one outcome summary. Because many of the observational studies yielded a Very Low GRADE score in each outcome cohort shown in Table II, we used the MERSQI score to better differentiate the quality of evidence of these studies (see Table I).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These groups were analyzed subsequently using the GRADE system in Table II. Six studies 9,20,25,28,29,31 reported on more than one outcome and were included in more than one outcome summary. Because many of the observational studies yielded a Very Low GRADE score in each outcome cohort shown in Table II, we used the MERSQI score to better differentiate the quality of evidence of these studies (see Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies included participants' perception and attitude toward coaching interventions and participants' opinions on their confidence and stress level after being coached. 9,17,25,29,31,34,37 On the basis of the GRADE evaluation, this outcome category received a Very Low strength of evidence and a mean MERSQI score of 10, the lowest mean compared with the other three outcome categories. The main factors driving this relatively low score were selection bias (voluntary enrollment), nonblinded observers and self-assessed outcome measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Publication in EM journals predominated (36; 75%). Three (6%) appeared in medical education journals, and nine (19%) were published in journals ranging from surgery 33,42,44,54 to psychiatry. 31,52 Others included palliative medicine, 26 critical care, 56 and simulation.…”
Section: Trends In Medical Education Research In 2012mentioning
confidence: 99%
“…The sources of funding were as follows: five federal (two NIH, one Canada, and one Taiwan), five universitysponsored, two industry-supported, and two organizationally funded. Research methodology included 17 surveys (36%), 17,19,21,25,30,31,33,37,40,42,46,[50][51][52]54,60,61 15 (31%) observational analyses, [14][15][16]22,23,27,32,33,38,44,47,49,56,57,59 and three (6%) qualitative methodology studies. 19,28,45 There were only 12 (25%) with an experimental or quasi-experimental study design, 20,24,26,35,36,39,41,43,48,53,55,57 with five of the highlighted articles using this rigorous design.…”
Section: Trends In Medical Education Research In 2012mentioning
confidence: 99%